METODE ECONOMIC VALUE ADDED (EVA) DAN RETURN ON ASSET (ROA) UNTUK ANALISIS KINERJA KEUANGAN PADA PT SARIMELATI KENCANA TBK - Asfar, Andi Hasryningsih; Kartika, Wika; Saputra, Saripudin; Fathoni, Malik (Yayasan Education and Social Center, 2024)
Financial performance is a description of activities to achieve business goals in a certain period. Performance measurement is a measurement activity carried out on various activities in the company. During the Covid-19 pandemic that attacked Indonesia, many companies experienced substantial losses and affected the company's financial performance. The purpose of this study is to determine and analyze the development of the financial performance of PT Sarimelati Kencana Tbk using the Economic Value Added (EVA) and Return on Asset (ROA) methods. This study uses a descriptive method with a qualitative approach. The data used in this study is secondary data, namely data collected indirectly, which was obtained through the financial report data of PT Sarimelati Kencana Tbk which is listed on the Indonesia Stock Exchange (IDX) in 2018-2021.The results of this study after calculations show that the value of Economic Value Added (EVA) and Return On Assets (ROA) fluctuates in each period of the year, especially in 2020 so that it affects the financial performance of PT Sarimelati Kencana Tbk.Based on the results of the analysis, it can be concluded that the Economic Value Added (EVA) and Return On Asset (ROA) methods show less effective performance so that there is a decrease in managing assets to generate company profits